The impact of using the strategy of the aquarium in solving the mathematical problems of the second grade students of mathematics (Journal of the College of Basic Education, 2022)
the aim of the research is to identify the effect of the aquarium strategy on solving mathematical problems among middle school students in mathematics. The research sample consisted of (60) students, they were divided into two groups, so the number of the experimental group was (30) students, and the number of the control group was (30) students from the intermediate school (July 14 for girls). The researcher conducted parity between them in the variables of previous knowledge, previous achievement, chronological age calculated in months. The researcher prepared an achievement test of (20) paragraphs, and after it was presented to a group of arbitrators, its validity was verified and it reached (0.88). By using the re-test method, the researcher verified its stability, and the stability factor was (0,81). The results showed that the difference between the two groups is in favor of the experimental group that used the aquarium strategy and thus rejects the hypothesis. For the presence of statistically significant differences in favor of the experimental group members.